2020
DOI: 10.1371/journal.pbio.3000603
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β cell microRNA-26a alleviates type 2 diabetes by improving peripheral insulin sensitivity and preserving β cell function

Abstract: Type 2 diabetes (T2D) is characterized by insulin resistance along with pancreatic β cell failure. β cell factors are traditionally thought to control glucose homeostasis by modulating insulin levels, not insulin sensitivity. Exosomes are emerging as new regulators of intercellular communication. However, the role of β-cell-derived exosomes in metabolic homeostasis is poorly understood. Here, we report that microRNA-26a (miR-26a) in β cells not only modulates insulin secretion and β cell replication in an auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 76 publications
1
104
0
Order By: Relevance
“…Intriguingly, it has recently been shown that phosphorylated STAT3 is present in exosomes from 5-fluorouracil (5-FU) resistant colorectal cancer cells, which contributes to acquired 5-FU resistance [ 149 ]. Given the importance and efficiency of exosomes in intercellular and interorgan communication [ 150 , 151 ], these findings not only add another complexity to STAT3 regulation, but also pave a new way to inhibit the oncogenic function of STAT3, as well as to delivery STAT3 inhibitors via exosomes.…”
Section: Targeting Stat3 For Cancer Immunotherapymentioning
confidence: 99%
“…Intriguingly, it has recently been shown that phosphorylated STAT3 is present in exosomes from 5-fluorouracil (5-FU) resistant colorectal cancer cells, which contributes to acquired 5-FU resistance [ 149 ]. Given the importance and efficiency of exosomes in intercellular and interorgan communication [ 150 , 151 ], these findings not only add another complexity to STAT3 regulation, but also pave a new way to inhibit the oncogenic function of STAT3, as well as to delivery STAT3 inhibitors via exosomes.…”
Section: Targeting Stat3 For Cancer Immunotherapymentioning
confidence: 99%
“…Diabetic complications are closely correlated with insulin resistance and may reflect the severity of pregestational diabetes and poor glycemic control. 55 Similarly, previous studies have found a higher risk of genital anomalies and cardiovascular diseases in offspring of mothers with diabetic complications. 21 33 Maternal poor glycemic control in pregnancy may exert potential implications in offspring for behavioral and emotional problems.…”
Section: Discussionmentioning
confidence: 82%
“…However, the secretion of miRNAs from the pancreas was not investigated until very recently. A study reported that β cell‐secreted miR‐26s influenced peripheral insulin sensitivity (Xu et al., 2020). Herein, we found that pancreatic β cells respond to high levels of FFAs by secreting exosomal miR‐29s to target the hepatic insulin signalling pathway and promote insulin resistance.…”
Section: Discussionmentioning
confidence: 99%